Dendritic cell vaccination in pediatric gliomas: lessons learnt and future perspectives - Matthias eEyrich; Matthias eWölfl; Johannes eRachor; Susanne C Schreiber; Paul G Schlegel (Frontiers Media S.A., 2013)
Immunotherapy of malignant gliomas with autologous dendritic cells (DC) in addition to surgery and radiochemotherapy has been a focus of intense research during the past decade. Since both children and adults are affected by this highly aggressive brain tumor, 10-15% of the several hundred vaccinated patients represent children, making pediatric glioma patients the largest uniform pediatric vaccination cohort so far. In general, DC vaccination in malignant gliomas has been shown to be safe and several studies with nonvaccinated controls could clearly demonstrate a survival benefit for the vaccinated patients. Interestingly, children and adolescents below 20 years of age seem to benefit even more than adult patients. This review summarizes the findings of the 25 clinical trials published so far and gives a perspective how DC vaccination could be implemented as part of multimodal therapeutic strategies in the near future.